Development Of Digital Literacy Skills Rubric at Primary School Level - (:unkn) unknown (T.C. Milli Egitim Bakanligi, 2019)
The purpose of this research was to develop a reliable and valid alternative assessment tool for the measurement of digital literacy skills at primary school level. The participants were 31 fourth-grade students in an elementary school located on the Anatolian side of Istanbul. The measurement instrument called New Literacy Skills Rubric was developed using ORCA (Online Reading Comprehension Assessment-Elementary), which was adapted and used by Kingsley (2011). The Digital Literacy Skills Rubric (DLSR), based on the new Literacy Skills and online reading comprehension, was developed using the ORCA (Online Reading Comprehension Assessment-Elementary), an adaptation tool used by Kingsley (2011). In the process of rubric development, in-class applications were carried out using the appropriate web sites in terms of content, usage, age level and reliability. The reliability of the rubric was tested using internal consistency coefficient, item analyses, Fleiss Kappa coefficient and inter-rater reliability. The validity was tested using expert opinions and pearson-product moment correlation. The evaluation of the results showed that a statistically valid and reliable rubric consisted of four parts and 12 questions was obtained. © 2019. All Rights Reserved.
Keywords: alternative assessment; digital literacy skills; Literacy; new literacy skills; online reading comprehension; rubric